2008
DOI: 10.4049/jimmunol.181.4.2414
|View full text |Cite
|
Sign up to set email alerts
|

Colonization with Heligmosomoides polygyrus Suppresses Mucosal IL-17 Production

Abstract: Helminth exposure appears to protect hosts from inappropriate inflammatory responses such as those causing inflammatory bowel disease. A recently identified, strongly pro-inflammatory limb of the immune response is characterized by T cell IL17 production. Many autoimmune type inflammatory diseases are associated with IL17 release. Because helminths protect from these diseases, we examined IL17 production in helminth-colonized mice. We colonized mice with Heligmosomoides polygyrus, an intestinal helminth, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
88
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 35 publications
3
88
1
Order By: Relevance
“…1 Collectively, these studies have shown that as a consequence of the host response to infection with helminth parasites, there is mobilization of transforming growth factor (TGF)-␤, interleukin (IL)-10, Foxp3 ϩ regulatory T cells, alternatively activated macrophages, and inhibition of IL-17-and interferon (IFN)-␥-driven events: one, or a combination, of these events could block the development of autoimmune and inflammatory disorders. [2][3][4][5][6][7] These findings have been complemented by intriguing data suggesting that infection with viable parasitic nematodes could be a treatment for patients with inflammatory bowel disease (IBD) 8 or asthma, 9 whose condition is not managed by conventional therapies.…”
mentioning
confidence: 87%
“…1 Collectively, these studies have shown that as a consequence of the host response to infection with helminth parasites, there is mobilization of transforming growth factor (TGF)-␤, interleukin (IL)-10, Foxp3 ϩ regulatory T cells, alternatively activated macrophages, and inhibition of IL-17-and interferon (IFN)-␥-driven events: one, or a combination, of these events could block the development of autoimmune and inflammatory disorders. [2][3][4][5][6][7] These findings have been complemented by intriguing data suggesting that infection with viable parasitic nematodes could be a treatment for patients with inflammatory bowel disease (IBD) 8 or asthma, 9 whose condition is not managed by conventional therapies.…”
mentioning
confidence: 87%
“…Furthermore, it has been reported that colonization with Heligmosomoides polygyrus suppresses IL-17 production in the mesenteric lymph node (14). Experimental studies in mouse models have also demonstrated that helminth infections can ameliorate autoimmune diseases (15)(16)(17), and although Th2 and antiinflammatory cytokines have been implicated in protection, the role of Treg cells is still unclear.…”
mentioning
confidence: 99%
“…Remarkably, MS-associated disease activity increases after treatment with anti-helminthic drugs (3). Studies in mouse models have demonstrated that infection with helminth parasites protects against autoimmune diseases mediated by IL-17-or IFN-g-secreting T cells (4)(5)(6)(7). We have reported that live infection with the helminth parasite Fasciola hepatica attenuated the clinical severity of experimental autoimmune encephalomyelitis (EAE) in a TGF-b-dependent manner and was associated with the expansion of Tregs (7).…”
mentioning
confidence: 99%